Synergism of carbon quantum dots and Au nanoparticles with Bi2MoO6 for activity enhanced photocatalytic oxidative degradation of phenol. Issue 46 (25th August 2021) - Zhao, Qiang; Zhang, Zhuangzhuang; Yan, Ting; Guo, Li; Yang, Chunming; Gao, Ge; Wang, Yu; Fu, Feng; Xu, Bin; Wang, Danjun
Abstract : Carbon quantum dot up-conversion emission and Au plasmon resonance effect synergetically promote the separation and migration of photogenerated electron e − /h + pairs of Bi2 MoO6, achieving efficient ROS for phenol photocatalytic mineralization. Abstract : Localized surface plasmon resonance (LSPR) offers an opportunity to enhance the efficiency of photocatalysis. However, the photocatalysts's plasmonic enhancement is still limited, as most metals/semiconductors depend on LSPR contribution of isolated metal nanoparticles. In the present work, carbon quantum dots (CQDs) and Au nanoparticles (NPs) were simultaneously assembled on the surface of a three-dimensional (3D) spherical Bi2 MoO6 (BMO) nanostructure with surface oxygen vacancies (SOVs). The collective excitation of CQDs and Au NPs demonstrated an effective strategy to improve the utilization of up-conversion emission and plasmonic energy. The contribution of CQDs and Au NPs assembled on the surface of BMO (7 wt% CQDs/Au/BMO) realized a photocatalytic phenol degradation enhancement (apparent rate constants, k app /min −1 ) of 56.5, 9.5 and 3.9, and 2.2-fold increase compared to BMO, BMO-SOVs, Au/BMO and CQDs/BMO, respectively. The as-fabricated 7 wt% CQDs/Au/BMO exhibited the highest mineralization rate for phenol degradation with 72.4% TOC removal rate in 120 min. The excellent photocatalytic performance of CQDs/Au/BMO was attributed to the synergistic effect of CQDs, Au NPs and SOVs. The CQD up-conversion emission synergetically boosts Au NPs' LSPR significantly promoting the separation and migration of photogenerated electron (e − )/hole (h + ) pairs, which could improve the oxygen molecule activation process and thereby their ability to generate reactive oxygen species (ROS). The present work is a step forward to understand and construct similar photocatalysts using an entirely reasonable hypothesis of activity enhancement mechanism according to the active species capture experiments and band structure analysis.